Citrullus lanatus is a New Natural Host of Groundnut ringspot virus in Brazil - Leão, Evelynne Urzêdo [UNESP]; de Almeida Spadotti, David Marques [UNESP]; Rocha, Kelly Cristina Gonçalves [UNESP]; de Fátima da CunhaPantoja, Késsia [UNESP]; Rezende, Jorge Alberto Marques; Pavan, Marcelo Agenor [UNESP]; Krause-Sakate, Renate [UNESP] (Wiley, 2015)
In 2012 and 2013, watermelon (Citrullus lanatus) plants from commercial crops in São Paulo State were found showing mosaic, necrotic lesions, leaf deformation and necrotic spots on the fruits, suggestive of tospovirus infection. Leaf and fruit samples were separately tested by PTA-ELISA and reverse transcription polymerase chain reaction (RT-PCR) against tospovirus was performed. The virus was identified as Groundnut ringspot virus (GRSV) and was sap transmissible. The host range was similar to isolates of GRSV found naturally infecting Solanaceae, except that this isolate infected watermelon systemically but did not infect tomato cvs. Santa Clara and Mariana. Thrips collected in the field transmitted GRSV to watermelon, sweet pepper and Nicotiana species. To our knowledge, this is the first report on the natural infection of watermelon by GRSV.
Keywords: Brazil; Groundnut ringspot virus; RT-PCR; Survey; Tospovirus; Watermelon